A música contemporânea de concerto e a reinvenção da análise musical - Costa, Jone Luiz Conceição da (2015)
This work is about musical analysis and its relation to the contemporary poetics. From the traditional idea of the analysis as a historical field of study, the research shows changes and matters between musical analysis and composition. Conceptual authors of this paper were Cook, Nattiez and Antenor Corrêa. Relevant works were considered to explain this way, and a set of three studies for guitar was composed especially for this research.